(untitled) (World Science, 2019)
A war correspondent has no border, no gender, no religion or race. The only thing a war reporter has - the skills of delivering truth, reflection of the reality in the way it is. The soviet space was absolutely closed to journalism and combat women journalists’ involvement in wars. The field almost consisted of males. Consequently, it seems impossible to analyze and compare the technique of writing of American and Soviet Women. If America freely accepts women for being actively involved in covering war activities, the Soviets obviously refused to do so. The role of a war correspondent is much bigger than one can suppose. Being a war reporter is more than implementing their responsibilities. It goes deeper into the history. A professional combat reporter is a historian facing the history and keeping it for the next generation. The paper considers advantages and disadvantages of being a female combat correspondent in the Soviet space and the United States of America. The role of American and Soviet women reporters in covering WWII.